The Influence of Self-Efficacy on Mathematical Understanding Ability in Elementary School Students - Wisnu Zakaria; Turmudi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The discovery of students who feel anxious, doubtful, and do not have confidence in learning mathematics has an impact on the low component of affection and also student achievement, the importance of Self-Efficacy is the trigger for this research. The purpose of this research is to determine the phenomenon of the influence and linkage of Self-Efficacy on the mathematical ability of elementary school students. This type of research is pre-experimental research with one-shot case study design. Data analysis using a mix of quantitative and qualitative analysis methods. Data retrieval techniques are taken with test techniques to measure mathematical understanding ability and non-test techniques such as filling out questionnaires and interviews. The results of this research were shown from inferential correlation and linear regression tests and concluded that: (1) self-efficacy has a significant relationship with students' mathematical understanding ability; (2) self-efficacy positively affects students' mathematical understanding ability; and (3) The findings show that students' self-efficacy is still low, as well as their learning outcomes, the trigger for low self-efficacy is thought to be due to the socio-cultural and economic background of students, aggravated by learning styles in schools that do not pay attention to the realm of student affection.